(untitled) (THE IRAQI JOURNAL FOR MECHANICAL AND MATERIALS ENGINEERING, 2019)
An experimental investigation involves the effect of the turning hollow-cylinder within a solar water distillation on the output of distillate water. This study is to be conducted in order to validate the optimum productivity of purification water by turning hollow-cylinder. The experiments were carried out in Kirkuk city, Iraq, 2018.Experimental results demonstrated that a basin water height is (1 cm) gives the better productivity of (1225 ml/ m2.day) for the conventional solar water distillation, and (2 cm) basin water height for the modification solar water distillation gives the optimum productivity which is (3540 ml/m2.day) which represent an increase of 188% when compared with the productivity of the conventional solar water distillation. 0.5 rpm and 1rpm are the optimum rpm for the hollow cylinder for the modification solar water distillation without and with flat plate solar water collector. The maximum percentage of productivity obtained from the modification solar water distillation which connected to a solar water heater with automatically varying speed according to the solar radiation intensity (Auto turning + Collector) gives more than (310%) enhancement. The estimated cost of one litre distillate water output for modification and conventional solar water distilleries were 136 ID and 175 ID respectively.